+0

0
403
5

sqrt{4-12x^2} is equal to (2 sqrt(sqrt(3)-3 x) sqrt(sqrt(3)+3 x))/sqrt(3)

what are the steps to get this answer

Guest Aug 23, 2015

#5
+85955
+8

√[4 - 12x^2] = 2√[√3 -3x]*√[ √3 + 3x] / √3   simplify

√[4 (1 - 3x^2] = 2 √ [ 3 - 9x^2] / √3

2 √[1 - 3x^2] = 2 √ [ 3 - 9x^2] / √3    divide both sides by 2

√[1 - 3x^2] = √ [ 3 - 9x^2] / √3  multiply both sides by √3

√3 * √[1 - 3x^2]  = √ [ 3 - 9x^2]

√[3[1 - 3x^2] ]  = √ [ 3 - 9x^2]

√[3 - 9x^2]  = √[ 3 - 9x^2]

And one side = the other side....just as asinus has said.....!!!!!

CPhill  Aug 23, 2015
Sort:

#1
+7257
+5

Hallo anonymous!

sqrt (4-12x^2)

sqrt (4-12x^2) = sqrt (4 * (1 - 3x²)) = 2 * sqrt (1 - 3x²)

= 2 * √(1- 3x²) = 2 * √[(1 + x√3) * (1 - x√3)]

sqrt (4-12x^2) = 2 * √[(1 + x√3) * (1 - x√3)]

Further calculations would result in no additional simplification.

:- )

asinus  Aug 23, 2015
#2
0

under alternate forms there is (2 sqrt(sqrt(3)-3 x) sqrt(sqrt(3)+3 x))/sqrt(3)

do you know how they got it?

Guest Aug 23, 2015
#3
0

on the wolframalpha website that is

Guest Aug 23, 2015
#4
+7257
+5

### Hello friends!

The whole backwards.

(2 sqrt(sqrt(3)-3 x) sqrt(sqrt(3)+3 x))/sqrt(3)

= (2 * √ ( √ (3) - 3x ) * √ ( √ (3) + 3x )) / √ (3)

= (2 √ (3 - 9x²)) / √ (3)

= √ ( 12 - 36 x²) / √ (3)

= ( √ (3) * √ (4 - 12 x²)) / √ (3)

= √ ( 4 - 12 x² )

√ ( 4 - 12 x² ) = (2 sqrt(sqrt(3)-3 x) sqrt(sqrt(3)+3 x))/sqrt(3)

# Q. E. D.

Greetings    :- )

asinus  Aug 23, 2015
#5
+85955
+8

√[4 - 12x^2] = 2√[√3 -3x]*√[ √3 + 3x] / √3   simplify

√[4 (1 - 3x^2] = 2 √ [ 3 - 9x^2] / √3

2 √[1 - 3x^2] = 2 √ [ 3 - 9x^2] / √3    divide both sides by 2

√[1 - 3x^2] = √ [ 3 - 9x^2] / √3  multiply both sides by √3

√3 * √[1 - 3x^2]  = √ [ 3 - 9x^2]

√[3[1 - 3x^2] ]  = √ [ 3 - 9x^2]

√[3 - 9x^2]  = √[ 3 - 9x^2]

And one side = the other side....just as asinus has said.....!!!!!

CPhill  Aug 23, 2015

### 36 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details